2012
DOI: 10.3390/md10030627
|View full text |Cite
|
Sign up to set email alerts
|

Chondrosterins A–E, Triquinane-Type Sesquiterpenoids from Soft Coral-Associated Fungus Chondrostereum sp.

Abstract: The marine fungus Chondrostereum sp. was collected from a soft coral Sarcophyton tortuosum from the South China Sea. This fungus was cultured in potato dextrose broth medium and the culture broth was extracted with EtOAc. Five new triquinane-type sesquiterpenoids, chondrosterins A–E (1–5), and the known sesquiterpenoid hirsutanol C (6), were isolated. The structures were elucidated mainly on the basis of NMR, MS, and X-ray single-crystal diffraction data. Chondrosterin A (1) showed significant cytotoxic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 8 publications
1
51
0
Order By: Relevance
“…The 1D NMR spectra data of 1 were similar to those of chondrosterin E [11], which was isolated from a coralassociated fungus Chondrostereum sp., except a methine at δ H (2.34, d, J = 2.5 Hz, H-2) and δ C (63.8, C-2) in chondrosterin E was replaced by an oxyquaternary carbon δ C (89.7, C-2) in 1. In the HMBC spectrum (Fig.…”
Section: Resultsmentioning
confidence: 72%
“…The 1D NMR spectra data of 1 were similar to those of chondrosterin E [11], which was isolated from a coralassociated fungus Chondrostereum sp., except a methine at δ H (2.34, d, J = 2.5 Hz, H-2) and δ C (63.8, C-2) in chondrosterin E was replaced by an oxyquaternary carbon δ C (89.7, C-2) in 1. In the HMBC spectrum (Fig.…”
Section: Resultsmentioning
confidence: 72%
“…The fungal species showed high cytotoxic activity against human liver carcinoma cell line (HEPG-2) with IC 50 value 18.8 µg/ml. In close relation, the culture filtrate extract of A. tritici isolated from the coral Galaxea fascicularis collected at Port Dickson, Malaysia, showed cytotoxic and antimicrobial activities (Sabdaningsih et al 2016 showed potent cytotoxicity against human lung cancer cell line A549, human nasopharyngeal carcinoma cell line CNE2 and human colon cancer cell line Lovo (Li et al 2012). The LC-MS fingerprints of the A. ochraceopetaliformis EtOAc extract…”
Section: Cytotoxicity Of Coral Reef Symbiotic Fungi Against Tumour Cementioning
confidence: 90%
“…Recent studies revealed that the cryptic biosynthetic pathways of fungi can be activated and the chemical diversity of their metabolites can be maximized by alternating their cultivation parameters systematically, such as the components of the media [1,2], co-culture [3,4], feeding precursors [5,6] and the addition of enzyme inhibitors [7,8]. For example, marine fungus Chondrostereum sp., which was isolated from soft coral Sarcophyton tortuosum , grows in different culture media and can produce various novel bioactive hirsutane-type sesquiterpenoids [9,10,11,12]. …”
Section: Introductionmentioning
confidence: 99%